Family formation and transition to parenthood trajectories along generations: the role of living in the residential care in Portugal - Artamonova, Alena (2019)
This study explored the role of living in residential care in family formation and transition to parenthood patterns in Portugal. It also evaluated the process of youngsters in care preparation for independent life. The life course tradition was chosen as the main framework with a focus on social ecology and demographical behavior determinants that were generated in this interdisciplinary study to explain trajectories of the Portuguese with and without the experience of living in the residential care homes. For tracing the trajectories of the Portuguese without living in care background, the quantitative data of European Social Survey-Round 3 and the methods of cluster analysis and descriptive statistics were applied. For tracing the trajectories of the Portuguese with living in care background and revealing the factors of their better life outcomes, participants were selected based on purposeful sampling and snow ball methods; their narratives were analyzed using lifeline analysis and thematic content analysis methods. For examining the process of preparation for independence, group interviews with 3 pairs of educators from Autonomization Apartments project were organized and collected data were analyzed using the SWOT technique. The trajectories of male informants look more “normal” in the context of trajectories of general population represented in ESS-Round 3 than the trajectories of female care leavers. Timing and sequence of transition to adulthood events of the informants from the young cohort do not seem aberrant. The three factors of care leaver’s better life outcomes were revealed: low traumatization, extended support network, and valued education. For older and young cohorts, the role of residential care was different because of multilevel changes in the country. Care leavers from older cohorts were empowered by means of education. Moreover, male Casa Pia leavers had a powerful support network represented by ‘brothers’ and casapianos from other cohorts. Women from older cohorts also could get education and support but their experiences in institutions sounded to be traumatizing. Young care leavers seem to lose the advantage of better education due to the democratization of education system in the country. However, they grow up in the de-institutionalized residential care context, can stay in care longer, gain practical skills for independent living, and use the support of professionals to deal with adversity.